Penghormatan Terhadap Leluhur: Perspektif Masyarakat Batak Kristen Terhadap Ritual Mangongkal Holi Di Desa Sinom Hudon Tonga - Nurjannah Sintya Sihotang; Megawati Manullang; Warseto Freddy Sihombing (Lumen: Jurnal Pendidikan Agama Katekese dan Pastoral, 2023)
The aim of this research is to find out the meaning of respect for ancestors contained in the mangongkal holi ritual of the Christian Batak community. The research method used is qualitative research with a socio-theological approach. The current understanding of the Christian Batak community regarding the mangongkal holi ritual is very different, especially after the arrival of Christianity to Batak land, some think that this ritual contains animism or something else and there are also those who think that this ritual is contrary to Christianity. This ritual cannot be said to be in conflict with Christianity, but on condition that in the ritual there is no hasipelebeguon or things related to ancestor worship because in essence, as a Christian Batak society, they must be able to balance ritual and religion. This research explains what the meaning and purpose of the mangongkal holi ritual is for the Batak people, how the ritual and things related to mangongkal holi are carried out and their relationship with Christianity, and this research also explains how ancestors are respected biblically and also in Toba Batak ways. The result of this research is to examine socio-theologically the mangongkal Holi ritual by taking the example of moving Joseph's bones, which is about how respect for ancestors is depicted.